Analysis Of Online Marketing Strategies In Increasing Sales Volume At Transcom Stores In Gunungsitoli City - Laia, Aluiwa'auri; Mendrofa, Yupiter; Harefa, Idarni; Kakisina, Sophia Molinda (Journal of Management, Economic, and Accounting, 2025)
This research, entitled "Analysis of Online Marketing Strategies in Increasing Sales Volume at Toko Transcom in Gunungsitoli City," aims to examine the implementation of online,  marketing strategies and identify the challenges faced by Toko Transcom in boosting its sales volume. This study employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The findings reveal that Toko Transcom has implemented various online,  marketing strategies such as promotions through social media platforms (Instagram, Facebook, and TikTok), the use of attractive visual content, and direct interaction with customers through digital channels. These strategies have proven to be quite effective in attracting consumer interest and increasing sales volume, particularly among the younger generation active on social media. However, the study also found several obstacles, such as the lack of human resources with professional digital marketing expertise, inconsistency in uploading promotional content, and technical difficulties in managing social media accounts. The research concludes that online,  marketing holds significant potential in boosting sales, but it requires support from a competent team and well-planned strategi.